A Novel Approach for Facial Attendance:AttendXNet - Arora, Kawal; Bist, Ankur Singh; Prakash, Roshan; Chaurasia, Saksham (Pandawan, 2020)
Recent advancements in the area of facial recognition and verification introduced the possibility of facial attendance for various use cases. In this paper we present a system named as AttendXNet. Our method uses the ResNet and Multi-layer feed forward network to achieve the state of art results. Extensive analysis of various deep learning and machine learning techniques is described. Face anti-spoofing is a major challenge in facial attendance. Extended-MobileNet is used to resolve the same issue. We also introduced the end to end pipeline to implement an attendance system for various use cases.